Dialectical Materialism or Dialectics of the Human?: Marxism and Animal Liberation Movement - Erhan Korkmaz (Uluslararası Halkbilimi Araştırmaları Dergisi)
With reference to the book “18 Theses on Marxism and Animal Liberation”, published by the Alliance for Marxism and Animal Liberation, which aims to create a point of consensus between Marxism and the anti-speciesism struggle, this article discusses the solidarity and conflict between Marxism and the anti-speciesism movement under the titles “Why should anti-speciesism be Marxist?” and “Why should Marxism be anti-speciesist?”. While Marxists describe anti-speciesists as being insensitive to capitalism's exploitation of labor, pro-bourgeois, and idealistic with metaphysical and moralistic tendencies, anti-speciesists describe Marxists as incoherent for reproducing today's industrial animal exploitation through consumption relations within the capitalism they criticize. In 2014, the Alliance for Marxism and Animal Liberation, an association of animal liberation movement and communist left activists from Germany and Switzerland, suggested that for Marxists to abandon their incoherence, they should not be in a network of consumption relations that reproduce animal exploitation and should address the domination of capitalism over animals in their analysis while anti-speciesists should work with the historical materialist method to analyze the material conditions of speciesism. While these proposals seem to establish a point of compromise without making vital compromises on either side, as the discussion section of the article will show, there are many points ripe for debate. This article will both present this ground for compromise by summarizing the Alliance for Marxism and Animal Liberation's critique and open it up for discussion.